Systematic review and consensus definitions for the Standardised Endpoints in Perioperative Medicine (StEP) initiative: infection and sepsis. (April 2019) - ,; Myles, Paul; Gan, Tang Joon; Kurz, Andrea; Peyton, Phil; Sessler, Dan; Tramèr, Martin; Cyna, Alan; De Oliveira, Gildasio S.; Wu, Christopher; Jensen, Mark; Kehlet, Henrik; et al.
Abstract: Background: Perioperative infection and sepsis are of fundamental concern to perioperative clinicians. However, standardised endpoints are either poorly defined or not routinely implemented. The Standardised Endpoints in Perioperative Medicine (StEP) initiative was established to derive a set of standardised endpoints for use in perioperative clinical trials. Methods: We undertook a systematic review to identify measures of infection and sepsis used in the perioperative literature. A multi-round Delphi consensus process that included more than 60 clinician researchers was then used to refine a recommended list of outcome measures. Results: A literature search yielded 1857 titles of which 255 met inclusion criteria for endpoint extraction. A long list of endpoints, with definitions and timescales, was generated and those potentially relevant to infection and sepsis circulated to the theme subgroup and then the wider StEP-COMPAC working group, undergoing a three-stage Delphi process. The response rates for Delphi rounds 1, 3, and 3 were 89% ( n =8), 67% ( n =62), and 80% ( n =8), respectively. A set of 13 endpoints including fever, surgical site, and organ-specific infections as defined by the US Centres for Disease Control and Sepsis-3 are proposed for future use. Conclusions: We defined a consensus list of standardised endpoints related to infection and sepsis for perioperative trials using an established and rigorous approach. Each endpoint was evaluated with respect to validity, reliability, feasibility, and patient centredness. One or more of these should be considered for inclusion in future perioperative clinical trials assessing infection, sepsis, or both, thereby permitting synthesis and comparison of future results.